From Accumulation to Degradation: Reprogramming Polyamine Metabolism Facilitates Dark-Induced Senescence in Barley Leaf Cells - Sobieszczuk-Nowicka, Ewa; Kubala, Szymon; Zmienko, Agnieszka; Małecka, Arleta; Legocka, Jolanta (Frontiers in Plant Science, 2016)
The aim of this study was to analyze whether polyamine (PA) metabolism is involved in dark-induced Hordeum vulgare L. ‘Nagrad’ leaf senescence. In the cell, the titer of PAs is relatively constant and is carefully controlled. Senescence-dependent increases in the titer of the free PAs putrescine, spermidine and spermine occurred when the process was induced, accompanied by the formation of putrescine conjugates. The addition of the anti-senescing agent cytokinin, which delays senescence, to dark-incubated leaves slowed the senescence-dependent PA accumulation. A feature of the senescence process was initial accumulation of PAs at the beginning of the process and their subsequent decrease during the later stages. Indeed, the process was accompanied by both enhanced expression of PA biosynthesis and catabolism genes and an increase in the activity of enzymes involved in the two metabolic pathways. To confirm whether the capacity of the plant to control senescence might be linked to PA, chlorophyll fluorescence parameters, and leaf nitrogen status in senescing barley leaves were measured after PA catabolism inhibition and exogenously applied γ-aminobutyric acid (GABA). The results obtained by blocking putrescine oxidation showed that the senescence process was accelerated. However, when the inhibitor was applied together with GABA, senescence continued without disruption. On the other hand, inhibition of spermidine and spermine oxidation delayed the process. It could be concluded that in dark-induced leaf senescence, the initial accumulation of PAs leads to facilitating their catabolism. Putrescine supports senescence through GABA production and spermidine/spermine supports senescence-dependent degradation processes, as verified by H2O2 production.